Relationships between deep-water polychaete fauna and environmental factors in the southeastern Gulf of California, Mexico - Méndez, Nuria (Scientia Marina, 2007)
Polychaetes inhabiting deep-sea soft bottoms in the southeastern Gulf of California were collected during four oceanographic cruises in 2000 and 2001 at a depth range of 732-2110 m. A total of 84 taxa, representing 32 families, were collected. The relationships between density, species number and diversity and depth, dissolved oxygen, temperature, granulometry and organic matter content in sediments were analysed. Cluster analyses and MDS plots based on density allowed faunal assemblages to be established for each environmental variable: 700-1100 m, 1100-1600 m, 1900-2100 m and 2100-2200 m (depth); 0.00-1.20 ml/L, 1.20-2.00 ml/L and 2.00-2.40 ml/L (oxygen); 2.0-2.5°C, 2.5-4.0°C, 4.0-6.0°C and 6-6.5°C (temperature); 8-16%, 16%-18% and 18-20% (organic matter), 20-30%, 60-70% and 80-100% (mud). Polychaetes were not distributed according to gradients of any of these environmental variables. The dominant and frequent species of each group were not restricted to unique assemblages. Results of a canonical correspondence analysis indicated that depth, oxygen and temperature were the main environmental variables responsible for polychaete distribution. The dominance of muddy sediments with high organic matter content (8.26 to 18.78%) throughout the study area reduces the importance of these parameters for polychaete distribution, since the dominant and frequent species belong to the detritivore families Ampharetidae, Maldanidae and Cirratulidae.